1968
DOI: 10.1103/physrev.174.624
|View full text |Cite
|
Sign up to set email alerts
|

Bounds for the Isothermal, Adiabatic, and Isolated Static Susceptibility Tensors

Abstract: Quantum-statistical proofs are given that the isolated (or Kubo) susceptibility tensor is positive indefinite and is bounded from above by the adiabatic susceptibility tensor, while the isothermal susceptibility tensor is positive definite and is bounded from below by the adiabatic susceptibility tensor. The results apply to either the static dielectric or magnetic cases. Biasing fields and permanent dipole moments may be present if desired. Criteria for equality of the various susceptibilities are established… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
1

Year Published

1970
1970
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 13 publications
2
35
0
1
Order By: Relevance
“…As a consequence, at the two-particle level specific differences emerge between the two models due to the intrinsic differences in the nature of the disorder: Specifically, the isothermal response of the systems, and hence its static susceptibility (Ω = 0), differs 59 due the absence/presence of a thermal-ensemble averaging of the scattering potential in the BM/FK (quenched/annealed disorder), respectively. In spite of this difference, we will demonstrate that the specific vertex anomalies found in the BM at Ω = 0 can be also observed in the FK model.…”
Section: Binary Mixture and Falicov-kimball Modelmentioning
confidence: 99%
“…As a consequence, at the two-particle level specific differences emerge between the two models due to the intrinsic differences in the nature of the disorder: Specifically, the isothermal response of the systems, and hence its static susceptibility (Ω = 0), differs 59 due the absence/presence of a thermal-ensemble averaging of the scattering potential in the BM/FK (quenched/annealed disorder), respectively. In spite of this difference, we will demonstrate that the specific vertex anomalies found in the BM at Ω = 0 can be also observed in the FK model.…”
Section: Binary Mixture and Falicov-kimball Modelmentioning
confidence: 99%
“…(26,34) as applied to the full cyclic process (i.e., changing in them t f → t ′ f ), Eq. (70) implies:…”
Section: VImentioning
confidence: 99%
“…• Only two features of the initial state ρ(t i ) were used: [H i , ρ(t i )] = 0 determined the specific form (26,27) of the work, while Eq. (23) was used in proving Θ m ≥ 0 in Eq.…”
Section: Now We Usementioning
confidence: 99%
See 1 more Smart Citation
“…But very soon it was noticed that spectral relations should be completed by a special treatment of the pole at zero frequency, which gives additional contribution connected with the presence of the conserving quantities [5][6][7]. Later, it was shown that such contributions describe the difference between the isothermal and isolated response of the many-body system and are specific for the non-ergodic systems [1,[6][7][8] where the regions exist in the phase space which cannot be achieved by the trajectory of the point that describes an evolution of the many-body system. In the Green's function formalism, the issue of ergodicity appears as a difficulty in determining the zero-frequency bosonic propagators [5][6][7][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%